Review on the degradation of GaN-based lateral power transistors - C. De Santi; M. Buffolo; I. Rossetto; T. Bordignon; E. Brusaterra; A. Caria; F. Chiocchetta; D. Favero; M. Fregolent; F. Masin; N. Modolo; A. Nardo; et al. (e-Prime: Advances in Electrical Engineering, Electronics and Energy, 2021)
Several mechanisms may contribute to the degradation of GaN transistors; in this paper we discuss the main processes that limit the lifetime of GaN power devices, with focus on the following relevant aspects: (i) the degradation/breakdown induced by off-state bias; (ii) the origin of vertical leakage and breakdown; (iii) the failure of the gate stack in MIS-HEMTs and in transistors with p-type gate. The data reviewed in this paper help the reader understanding the main issues related to the development of GaN-based transistors, and give hints on possible strategies to improve device reliability. The signatures of the main deep levels in gallium nitride, which can influence the reliability of the devices, are critically reviewed and summarized.